Improved modeling of cloudy‐sky actinic flux using satellite cloud retrievals. Issue 3 (9th February 2017) - Ryu, Young‐Hee; Hodzic, Alma; Descombes, Gael; Hall, Samuel; Minnis, Patrick; Spangenberg, Douglas; Ullmann, Kirk; Madronich, Sasha
Abstract: Clouds play a critical role in modulating tropospheric radiation and thus photochemistry. We develop a methodology for calculating the vertical distribution of tropospheric ultraviolet (300–420 nm) actinic fluxes using satellite cloud retrievals and a radiative transfer model. We demonstrate that our approach can accurately reproduce airborne‐measured actinic fluxes from the 2013 Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS) campaign as a case study. The results show that the actinic flux is reduced below moderately thick clouds with increasing cloud optical depth and can be enhanced by a factor of 2 above clouds. Inside clouds, the actinic flux can be enhanced by up to 2.4 times in the upper part of clouds or reduced up to 10 times in the lower parts of clouds. Our study suggests that the use of satellite‐derived actinic fluxes as input to chemistry‐transport models can improve the accuracy of photochemistry calculations. Key Points: Satellite cloud retrievals are used in a radiative transfer model to simulate cloudy‐sky actinic flux in the U.S. Clouds significantly attenuate and/or enhance actinic fluxes relative to cloud‐free skies Satellite‐constrained actinic fluxes capture well in situ airborne measurements from SEAC 4 RS where cloud‐sky conditions represent more than 60% of the total data